Modeling water allocation between wetlands and irrigated agriculture: case study of the Gediz Basin, Turkey - Voogt, K. de; Kite, Geoff; Droogers, Peter; Murray-Rust, Hammond (International Water Management Institute, 2000)
This report investigates how much water is required to maintain the freshwater reed beds that are the main shelter and breeding place for threatened bird species. The ability of Gediz basin to fulfill this requirement and the effects of this requirement on irrigated agriculture, the major competitor for water in the Gediz basin were subsequently examined.